Berkiprah dengan Kelembagan Politik Tradisional di Kabupaten Barru Sulawesi-Selatan (Studi Sejarah dan Antropologi Politik) - Andi M. Anwar Zaenong (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2018)
The origin of tradisional politics in Barru District can be known from the stereotype saying, “ Datu ri Tenete, Petta ri Berru, sibawa Mallusetasi, Arung ri Soppeng Riaja , “ (Datu King in Tanete, Petta King in Barru and Mallusetasi, Arung King in Soppeng Riaja). It is these three titles that manifest in the order of colonial politics in sub districs (Swapraja) throughout Barru area. In the Dutch colonial era, the government in the area called onderafdeling. However, after the emergence of Indonesian Republic, the tradisional system was slowly but surely changed by modernization and eventually hard to preserve. Therefore, reactualization is needed to anticipate all changes posed by globalization. Intitution of custom (Lembaga Adat) is actually a pa-rameter of self dignity in a nation. Therefore, re-establishing the institution of custom in Barru District is very significant in accordance with the regulation based on 1945 constitution, chapter 32, and also as follow-up of National policy in Regulation No. 10 Year 1993 on the Right of Cultural Preservation. The institution of custom comprises some committees of the heirs of custom order, that is, the descendarts of the King, not those who participated in the colonial politics.